Evaluation of heat of hydration of concrete containing high volume palm oil fuel ash - Abdul Awal, A.S.M.; Shehu, I.A. (Elsevier, 2013)
Pozzolanic materials, either naturally occurring or artificially made, have long been in practice since the early civilization. In recent years, the utilisation of pozzolanic materials in concrete construction has become increasingly widespread, and this trend is expected to continue in the years ahead because of technological, economical and ecological advantages of the materials. One of the latest additions to the ash family is palm oil fuel ash, a waste material obtained on burning of palm oil husk and palm kernel shell as fuel in palm oil mill boilers, which has been identified as a good pozzolanic material. This paper highlights test results on the performance behaviour of high volume palm oil fuel ash (POFA) in reducing the heat of hydration in concrete. Four concrete mixes namely OPC concrete i.e. concrete with 100% OPC as control, and high volume concrete i.e. concrete with 50%, 60% and 70% POFA were prepared, and the temperature rise due to heat of hydration in all the mixes was recorded. It has been found that palm oil fuel ash significantly reduced the total temperature rise in concrete. The result obtained and the observation made clearly demonstrate that the high volume replacement of cement by palm oil fuel ash is advantageous, particularly for mass concrete where thermal cracking due to excessive heat rise is of great concern.